2017
DOI: 10.1039/c6cc09788j
|View full text |Cite
|
Sign up to set email alerts
|

Access to thiopyrano[2,3-b]indole via tertiary amine-catalyzed formal (3+3) annulations of β′-acetoxy allenoates with indoline-2-thiones

Abstract: DABCO-catalyzed formal (3+3) annulations of β'-acetoxy allenoates with indoline-2-thiones are described, which provide facile access to thiopyrano[2,3-b]indole under mild reaction conditions. The reaction might proceed via the S2'-S2'-type process between β'-acetoxy allenoate and indole-2-thiolate with the assistance of the DABCO catalyst and KCO additive, followed by intramolecular Friedel-Crafts reaction at the 3-position of indole and central carbon of allene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Indoline-2-thiones 185 were selected as ideal candidates, showing 1,3-bisnucleophilic nature in the presence of a weak base. Thus, reaction of 194,195 Metal species are also reported to promote isomerization of allenols to dienes in both equimolecular and catalytic manner. The cobalt-catalyzed regioselective C8 dienylation of quinoline N-oxides with allenylcarbinol carbonates has been reported by Volla and co-workers, while the use of unprotected allenylcarbinols as the dienylating agents resulted in diminished yields.…”
Section: Enantioenriched Allenolsmentioning
confidence: 94%
See 1 more Smart Citation
“…Indoline-2-thiones 185 were selected as ideal candidates, showing 1,3-bisnucleophilic nature in the presence of a weak base. Thus, reaction of 194,195 Metal species are also reported to promote isomerization of allenols to dienes in both equimolecular and catalytic manner. The cobalt-catalyzed regioselective C8 dienylation of quinoline N-oxides with allenylcarbinol carbonates has been reported by Volla and co-workers, while the use of unprotected allenylcarbinols as the dienylating agents resulted in diminished yields.…”
Section: Enantioenriched Allenolsmentioning
confidence: 94%
“…Thus, reaction of 1-acetoxy-2-allenoates 183 and indolines 185 in the presence of DABCO provided dihydrothiocarbazoles 186 through a S N 2′–S N 2′ reaction sequence (Scheme ). , …”
Section: Synthetic Utilitymentioning
confidence: 99%
“…In the year 2017, Tong et al . reported the (3+3) annulation of β′ ‐acetoxy allenoate with indoline‐2‐thione (Scheme 1b) and observed that the annulation was initiated by the addition of sulfur anion to the diene‐ammonium intermediate at the β′ ‐carbon of the key intermediate [6j] . Iminoindolines (indoline‐2‐imines) have a structure similar to indoline‐2‐thiones.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first example of phosphine-catalyzed [3 + 2] cycloaddition reported by Lu in 1995, a wide variety of nucleophilic phosphine-catalyzed annulation reactions of allenoates has emerged as a powerful method for constructing synthetically valuable carbo- and heterocycles. , Among them, the Tong group has realized several Lewis base catalyzed annulations of β′-acetoxy allenoates via introduction an acetate group at the β′-position of 2,3-butadienoate. , In these cases, β′-acetoxy allenoate can be converted into a 2-phosphonium diene or 2-aminium diene intermediate via an addition–elimination process under phosphine catalysis or amine catalysis (Scheme ), allowing for the achievement of biselectrophilic reactivity of allenoates. Here, we report our studies on the development of a novel sequential phosphine catalyzed process of β′-acetoxy allenoates with p -QMs, In this manner, enyne intermediate A is first formed in situ under the phosphine catalyst, and then phosphine catalysis can promote 1,6-addition/annulation of p -QMs with intermediate A to construct chroman and tetrahydroquinoline skeletons bearing an all-carbon α-alkynyl quaternary center (Scheme ).…”
mentioning
confidence: 99%